IKTIKAD BAIK DALAM PERMOHONAN PEMBUATAN AKTA NOTARIIL DI WILAYAH KABUPATEN SLEMAN YOGYAKARTA - , WARDATUL FITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Research aims to know of notary public parameters used in determining an authentic deed applicants who has good faith or not and to know responsibility of notary due to deed at the request of an applicant who does not has a good faith. This research uses juridical and empirical methods, namely approach to a problem with to look and see norm applicable connected by phenomenomes that existed from the problems encountered in the field. Data collection was conducted in two ways: field research and library research. Analysis of data used are qualitative analysis outlined in the description descriptive. This research result indicates that first, in determining the characteristic of a applicants notariil deed with good faith is analyzing the decent intentioned of the parties that to propose deed notariil based on logic of law. So a notary not only seen data subjects ( identity ) the parties are already in accordance with the people who overlooks at notary public, listen to and examine the wishes or will the parties however, a notary needed to ensure that the wishes or will the parties that worthy of and deserving based on rationality in logic of law can be made the deed notariil and shall not in contrary with legislative regulations, of decency, and public order. Second, responsibility due to the making of a notarial deed upon the request of an applicant who is about good faith deed parties only limited on the formal course, because a notary just pour the will or desires the parties in a notarial deed with obligations provide counseling laws against the parties before poured in deed notariil. It was different against responsibility on ambtelijk a notarial deed, which includes the truth of the aspect of formal and facets materially such deed.